John Brown, Rose and the midnight cat - Wagner, Jenny; Brooks, Ron ((New York) : Puffin, 1977)
Rose's dog feels he can look after her without any help from a cat, but Rose has different ideas.
Booklist.
Bulletin (Center for Children's books).
School Library Journal.
2.2
K-3.
K-3
Keywords: Cats -- Fiction; Dogs -- Fiction; Friendship -- Fiction; Cats -- Fiction; Dogs -- Fiction; Friendship -- Fiction